2018
DOI: 10.3390/technologies6040119
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy in Robot-Assisted Training: Current Trends, Needs and Challenges

Abstract: In this article, we present a taxonomy in Robot-Assisted Training; a growing body of research in Human–Robot Interaction which focuses on how robotic agents and devices can be used to enhance user’s performance during a cognitive or physical training task. Robot-Assisted Training systems have been successfully deployed to enhance the effects of a training session in various contexts, i.e., rehabilitation systems, educational environments, vocational settings, etc. The proposed taxonomy suggests a set of catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Although formal cognitive training is uncommon in the robotics literature (but see Tsiakas et al 72 ), there is broad interest in providing direct IADL assistance, often in the form of reminders to complete daily living tasks. For example, medication reminding systems have been used to address older adults' reported desire to receive robotic assistance with medication management.…”
Section: Car Interventionsmentioning
confidence: 99%
“…Although formal cognitive training is uncommon in the robotics literature (but see Tsiakas et al 72 ), there is broad interest in providing direct IADL assistance, often in the form of reminders to complete daily living tasks. For example, medication reminding systems have been used to address older adults' reported desire to receive robotic assistance with medication management.…”
Section: Car Interventionsmentioning
confidence: 99%
“…In addition, based on this review, we identified HRI elements and game design fundamentals to propose a novel taxonomy that helps to classify and categorize important components used in multiplayer HRI scenarios covering considerations from a robot-oriented perspective (e.g., role, appearance, motor abilities) as well as game design elements (e.g., mechanics, feedback, technology, application field). Other HRI taxonomies have been proposed to (i) better define human-robot interrelations [97], (ii) identify opportunities for robot-assisted training systems [84], (iii) categorize action representations in robotics [99], (iv) promote the inclusion of ethical guidelines in HRI research [75], and (v) improve interface design and user experience in teleoperation applications in games [60]. The new taxonomy proposed in this article unveils not only the fundamental elements to consider when designing games (in particular multiplayer games) in HRI scenarios, but also provides a comprehensive description and illustrative definitions of each category, which contributes to the body of knowledge of the convergence between HRI and game user research.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the categories for data analysis, we integrated and adapted the HRI taxonomies from previous studies (Yanco and Drury, 2004;Bethel and Murphy, 2010;Salter et al, 2010;Tsiakas et al, 2018;Baraka et al, 2020;Onnasch and Roesler, 2020) and annotated the papers by the predefined categories. We describe below the different annotations used.…”
Section: Coding Frameworkmentioning
confidence: 99%
“…Goodrich and Schultz (2007) identified HRI roles, which were adopted by other researchers (Yanco and Drury, 2004;Tsiakas et al, 2018;Onnasch and Roesler, 2020). Based on their classification, 12 distinct participant's roles and eight robot's roles were defined.…”
Section: Participant's and Robot's Rolementioning
confidence: 99%